Research on the Nonlinear Characteristics of Acoustic Emission and Damage Mechanism of Gassy Coal under Unloading Conditions - Jie Liu; Qiuping Li; Ran Zhang; Zaiquan Wang; Shouqing Lu; Zhanyou Sa; Hao Wang (Geofluids)
Coal mining and production activities lead to static loading and unloading changes of coal stress in front of the working face, and the stress change process has a significant influence on the occurrence and development of coal-rock gas dynamic disasters. In this paper, the macroscopic failure characteristics, acoustic emission timing characteristics, and acoustic emission nonlinear characteristics of coal with different gas pressures under true triaxial loading and unloading conditions were experimentally studied. The results showed that the macroscopic failure form of coal with different gas pressures under unloading conditions was tensile-shear composite failure, and the crack structure was formed near the unloading surface. The fractal dimension D and multifractal parameter Δα of acoustic emission time series both could reflect the complexity of coal fracture process. With the increase of gas pressure, the fractal dimension D and multifractal parameter Δα decreased, which indicated that the greater the gas pressure, the lower the complexity of coal fracture process. Under different gas pressures, the dynamic change trends of multifractal parameter Δα were similar, taking the beginning of unloading as the dividing point, the change was roughly in the form of “W.” When the stress state and failure form of coal body changed, the multifractal parameter Δα changed synchronously, indicating that the change of Δα could reflect the transformation process of failure mechanism of coal body under load to a certain extent, which was of great significance for clarifying the occurrence and development mechanism of coal-rock gas dynamic disasters and ensuring the safe production in underground coal mines.